2020
DOI: 10.1371/journal.pone.0235479
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasound-guided transbronchial needle aspiration versus mediastinoscopy for mediastinal staging of lung cancer: A systematic review of economic evaluation studies

Abstract: Introduction The emergence of endobronchial ultrasound (EBUS) changed the approach to staging lung cancer. As a new method being incorporated, the use of EBUS may lead to a shift in clinical and costs outcomes. Objective The aim of this systematic review is to gather information to better understand the economic impact of implementing EBUS. Methods This review is reported according to the PRISMA statement and registered on PROSPERO (CRD42019107901). Search keywords were elaborated considering descriptors of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
4
0
5
Order By: Relevance
“…5,6 A small prospective randomized trial did not find any additive value of performing EUS in patients who first underwent EBUS. 29 Randomized trials 30,138 and aggregate data from these MAs demonstrate that endoscopic-based staging is at least equivalent to mediastinoscopy and is more cost-effective, 139,140 at least when used as the first staging modality. A 2017 decision analysis suggests that the cost-effectiveness of EBUS-based mediastinal staging varies by the pretest probability of N2 disease with mediastinal staging not cost-effective in clinical N0 patients if the probability of N2 involvement is very low (< 2.5%).…”
Section: Recommendationsmentioning
confidence: 99%
“…5,6 A small prospective randomized trial did not find any additive value of performing EUS in patients who first underwent EBUS. 29 Randomized trials 30,138 and aggregate data from these MAs demonstrate that endoscopic-based staging is at least equivalent to mediastinoscopy and is more cost-effective, 139,140 at least when used as the first staging modality. A 2017 decision analysis suggests that the cost-effectiveness of EBUS-based mediastinal staging varies by the pretest probability of N2 disease with mediastinal staging not cost-effective in clinical N0 patients if the probability of N2 involvement is very low (< 2.5%).…”
Section: Recommendationsmentioning
confidence: 99%
“…Several studies have compared the cost-effectiveness and safety of EBUS-TBNA for diagnosis versus mediastinoscopy 13 , 14 . Certainly according to current guidelines for lung cancer PET-CT and EBUS-TBNA have an algorithm before mediastiscopy is performed 15 .…”
Section: Discussionmentioning
confidence: 99%
“…COST Motta et al [83] reported lower cost for EBUS compared with mediastinoscopy [84]. Between 2007 and 2015, the mean cost of EBUS-TBNA in the USA was $2211 less than mediastinoscopy ($6816 versus $9023; P < 0.001).…”
Section: Safetymentioning
confidence: 99%